User controlled environment - Pinninti, Ashish (Kansas State University, 2015)
The mobile world is rapidly changing: Smartphones have gone from portable messaging and email devices to streaming-video machines that surf the Web at blazing speed. Now-a-days a smartphone can provide computing capabilities, wireless communication capabilities, run software and perform other tasks just like any traditional computer. These amazing features of a smartphone and Open Source Android market helped in the development of this project. The purpose of this project is to develop an Android application for controlling various elements of user environment. User Controlled Environment is an Android application for home. The environment consists of smart lights, an Android mobile devices for playing music and a display. The application sends the user’s preferred settings to the environment and the respective settings are applied. The preferences are displayed on the screen. The user will be able to view and adjust a variety of environmental preferences. The preferences include the light’s color, light intensity, and the music. When the user exits the application the environment goes to a default state. The users can set preferences which include moods, seven colors of light, three levels of light intensity and songs that the users can select.
Keywords: Phillips hue lights; Android; Mobile application; Representational state transfer; Home automation; Computer Science (0984)